A SYSTEMATIC REVIEW OF THE APPLICATION OF VIRTUAL OBJECTS IN LEARNING - Nurbekova Ж.К.; Baymendinova А.Н. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The education system is constantly evolving, using a virtual environment to improve the educational process. The use of virtual objects allows you to quickly and easily explain a large amount of theoretical material, and also allows students to learn effectively. Researchers have studied the benefits of a virtual environment and applications in various fields. Great interest of researchers was aroused by the fact that the virtual environment has great opportunities when using it in education. This article presents the results of a systematic review of scientific sources in the world scientific resources related to the use of virtual objects in education. The study examines the use of virtual objects in education not only as an educational tool, but also as an object of learning, and also conducts a quantitative and descriptive analysis of the results of the study. An analysis is made of the use of virtual learning objects in secondary education and aspects of their application in education. As a result, it was found that objects based on virtual reality increase the efficiency of their use in the learning process and the motivation of students to learn.